International publication trends in the Journal of Applied Behavior Analysis: 2000–2014. Issue 2 (23rd December 2015) - Martin, Neil T.; Nosik, Melissa R.; Carr, James E.
Abstract : Dymond, Clarke, Dunlap, and Steiner's (2000) analysis of international publication trends in the Journal of Applied Behavior Analysis ( JABA ) from 1970 to 1999 revealed low numbers of publications from outside North America, leading the authors to express concern about the lack of international involvement in applied behavior analysis. They suggested that a future review would be necessary to evaluate any changes in international authorship in the journal. As a follow‐up, we analyzed non‐U.S. publication trends in the most recent 15 years of JABA and found similar results. We discuss potential reasons for the relative paucity of international authors and suggest potential strategies for increasing non‐U.S. contributions to the advancement of behavior analysis.